1996
DOI: 10.1093/jnci/88.8.519
|View full text |Cite
|
Sign up to set email alerts
|

p53 Expression: Predicting Recurrence and Second Primary Tumors in Head and Neck Squamous Cell Carcinoma

Abstract: The expression of p53 protein in primary head and neck squamous cell carcinoma was significantly predictive of shorter survival because of its association with earlier development of both tumor recurrence and second primary tumors. Thus, p53 expression may be a valuable marker for identifying individuals at high risk of developing a recurrence of primary disease and second primary tumors who may benefit from adjuvant therapy and chemoprevention after definitive local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
2
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 37 publications
9
94
2
11
Order By: Relevance
“…2 In human cancers, accumulation of p53 has been shown to be a good indicator of poor prognosis. 10,13,20 In this study, we found p53 expression in 46% of the 140 tumors investigated, which is lower than the reported 64% 31 but similar to that 23,32 found in head and neck cancers, when examined using the same antibody and cutoff value. Our data, however, confirmed the results of previous studies that failed to establish an association of p53 expression with survival in head and neck cancers.…”
Section: Molecular Marker Expression In Oral Cancer M Shiraki Et Alsupporting
confidence: 59%
See 1 more Smart Citation
“…2 In human cancers, accumulation of p53 has been shown to be a good indicator of poor prognosis. 10,13,20 In this study, we found p53 expression in 46% of the 140 tumors investigated, which is lower than the reported 64% 31 but similar to that 23,32 found in head and neck cancers, when examined using the same antibody and cutoff value. Our data, however, confirmed the results of previous studies that failed to establish an association of p53 expression with survival in head and neck cancers.…”
Section: Molecular Marker Expression In Oral Cancer M Shiraki Et Alsupporting
confidence: 59%
“…5,6 Epidermal growth factor receptor (EGFR), a transmembranous protein that binds to ligands such as EGF and transforming growth factor-a, activates protein-tyrosine kinase, which mediates the signaling involved in cell proliferation and differentiation. 7 Apart from the well-established prognostic indicators of TNM staging and mode of invasion, these markers have high prognostic values in human cancer, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] although there are some discrepancies. [22][23][24] In view of the prospective impact of multiple molecular marker accumulation on tumor progression, multiple-marker testing could provide us with more useful information for our definition of the biological behavior of oral cancer than single marker expression.…”
mentioning
confidence: 99%
“…Studies indicate that the presence of p53 mutations may also be indicative in SCCHN of a higher frequency of, and shorter median time to, recurrence of the tumor (Brachman, 1994). In a recent study Shin et al also reported that higher levels of mtp53 expression in primary SCCHN, due presumably to the stabilization and longer half-life of the mutant form of the protein, were associated with both earlier recurrence and development of second primary tumors and could be an important adverse prognostic factor for survival (Shin et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…p53 and HPV-HR have been examined in association with HNC prognosis with conflicting results observed (19). Overexpression of p53 was related to worse prognosis in some investigations (3,5,20) but not in others (4,17), whereas HPV-HR has been associated with better prognosis (7,21). Studies of cervical cancer have not been able to address the p53/HPV relationship with survival because HPV-HR is a necessary cause of these tumors and thus cannot serve as a model for predicting outcomes.…”
Section: Introductionmentioning
confidence: 99%